The underground railroad : a novel - Whitehead, Colson, 1969- (New York : Doubleday, 2016)
A magnificent tour de force chronicling a young slave's adventures as she makes a desperate bid for freedom in the antebellum South
Cora is a slave on a cotton plantation in Georgia. When Caesar, a recent arrival from Virginia, tells her about the Underground Railroad, they decide to take a terrifying risk and escape. Though they manage to find a station and head north, they are being hunted. Their first stop is South Carolina, in a city that initially seems like a haven. But the city's placid surface masks an insidious scheme designed for its black denizens. And even worse: Ridgeway, the relentless slave catcher, is close on their heels
National Book Award, 2016
Keywords: 1800-1899; Underground Railroad -- Fiction; Fugitive slaves -- United States -- Fiction; FICTION / Literary; FICTION / Historical; FICTION / African American / General; Fugitive slaves; Underground Railroad; United States -- History -- 19th century -- Fiction; United States; Historical fiction; Historical fiction; Fiction; History